Energy storage and heat extraction – From thermally activated building systems (TABS) to thermally homeostatic buildings. (May 2015) - Ma, Peizheng; Wang, Lin-Shu; Guo, Nianhua
Abstract: The trend toward high envelope R- value for building energy efficiency made sense because at the starting point when the trend began in 1980s and 1990s buildings were poorly insulated. The advantage of high performance envelope was based on the consideration of envelope heat transfer and building heat balance (balance between heat transfer loss and fuel heat production). However, high performance envelope is not the silver bullet to building energy efficiency. A more comprehensive consideration of building energy efficiency should take into account of energy storage and heat extraction. In this paper we present a review of engineering literature on these two related topics: energy storage with special focus on thermally activated building systems (TABS) as the example of energy storage; heat extraction with the idea of homeostasis providing the context in the application of heat extraction. TABS combines the advantage of radiant surface heating and cooling and the utilization of building structure as thermal energy storage. This proved to be a critical step. This critical review argues that the hydronic circuit for radiant surface cooling offers the necessary element for extracting heat from indoor, thus, makes it possible for combining radiant conditioning, energy storage, and general practice of heat extraction—the resulting synergy of which will be called homeostasis in buildings.